The catch ebook A novella. - Herron, Mick (Slough House, 2020)
British spy master Mick Herron returns with an explosive novella set in the same world as his multiple CWA Dagger–winning Slough House series John Bachelor is the saddest kind of spy: not a joe in the field, not even a desk jockey, but a milkman—a part-time pension administrator whose main job is to check in on aging retired spies. Late in his career and having lost his wife, his house, and his savings after a series of unlucky choices, John's been living in a dead man's London apartment, hoping the bureaucracy isn't going to catch up with him and leave him homeless. But keeping a secret among spies is a fool's errand, and now John has made himself eminently blackmailable.